2015
DOI: 10.1016/j.bjhh.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a confirmatory RhD test on the correct serologic typing of blood donors

Abstract: BackgroundThe RHD gene is highly polymorphic, which results in a large number of RhD variant phenotypes. Discrepancies in RhD typing are still a problem in blood banks and increase the risk of alloimmunization. In this study, the RhD typing strategy at a blood bank in Brazil was evaluated.MethodsOne-hundred and fifty-two samples typed as RhD negative and C or E positive by routine tests (automated system and indirect antiglobulin test using the tube technique) were reevaluated for RhD status by three methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…When the number of genotyped weak D type 1, 2 or 3 types is calculated over all genotyped weak D, frequencies range from 87% in Croatia to 100% in Albania . Several reasons can be invoked to explain such discrepancies: (1) anti‐D serology tests used traditionally for donors in the blood banks, resulting in weak D type 1, 2 or 3 samples being mistyped as positive for the first‐level screening (therefore, no second‐level confirmation is performed); (2) different monoclonal anti‐D are used among different studies; (3) some studies calculate frequency percentages using the serological weak D samples as total number of samples, while others use the genotyped weak D samples as total number of samples; (4) studies have different sample sizes and origins; (5) inclusion of samples because of anti‐D production ; and (6) DEL samples .…”
Section: Discussionmentioning
confidence: 99%
“…When the number of genotyped weak D type 1, 2 or 3 types is calculated over all genotyped weak D, frequencies range from 87% in Croatia to 100% in Albania . Several reasons can be invoked to explain such discrepancies: (1) anti‐D serology tests used traditionally for donors in the blood banks, resulting in weak D type 1, 2 or 3 samples being mistyped as positive for the first‐level screening (therefore, no second‐level confirmation is performed); (2) different monoclonal anti‐D are used among different studies; (3) some studies calculate frequency percentages using the serological weak D samples as total number of samples, while others use the genotyped weak D samples as total number of samples; (4) studies have different sample sizes and origins; (5) inclusion of samples because of anti‐D production ; and (6) DEL samples .…”
Section: Discussionmentioning
confidence: 99%
“…Donors who are identified as D− on both anti‐D reagents are subjected to weak D testing utilizing the antihuman globulin phase. Donors should be labelled as D− only if the weak D test is negative .…”
Section: Rh Systemmentioning
confidence: 99%
“…It is consensus that molecular techniques allowed the start of a new stage of blood donor typing, including several strategies to identify RhD variants that are potentially immunogenic in apparently RhD-negative donors, as shown in several studies. 11 , 12 , 13 , 14 , 15 , 16 , 17 Furthermore, in some of these studies, these variants were also found to be associated with the C and E antigens of the Rh system, 11 , 12 , 14 , 15 although some RhD subtypes were found in ccee individuals. 13 Techniques have now identified more than 200 variants of the D antigen, including weak D, D partial and DEL types.…”
mentioning
confidence: 90%
“…A study by Schmidt et al 14 showed positive results for the RhD antigen in 5.9% of 152 blood donors – who had been previously identified as RhD negative in routine examinations – when using anti-D IgG monoclonal antibodies (clones ESD1, MS-26 and TH-28) in gel cards. In the same study, the authors evaluated another population of 4897 donors from different regions of Minas Gerais state, Brazil, who had all been previously phenotyped as D negative in the indirect antiglobulin test (IAT), with clones MS-26 and TH-28, and 70 (1.43%) individuals showed weak reactivity with ESD1 anti-D antibodies.…”
mentioning
confidence: 99%